2013
DOI: 10.1021/am4047393
|View full text |Cite
|
Sign up to set email alerts
|

pH-Induced Reversible Wetting Transition between the Underwater Superoleophilicity and Superoleophobicity

Abstract: Surfaces with controlled oil wettability in water have great potential for numerous underwater applications. In this work, we report a smart surface with pH-responsive oil wettability. The surface shows superoleophilicity in acidic water and superoleophobicity in basic water. Reversible transition between the two states can be achieved through alteration of the water pH. Such smart ability of the surface is due to the cooperation between the surface chemistry variation and hierarchical structures on the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(89 citation statements)
references
References 65 publications
2
86
0
1
Order By: Relevance
“…Following this strategy, many mesh and porous materials that are underwater superoleophobic have been fabricated, and these materials have been successfully applied in oil-water separation. [18][19][20][21][22][23][24][25] For example, Jiang and co-workers coated microscale porous stainless steel mesh with a nanostructured hydrogel to give a novel underwater superoleophobic rough mesh. [ 18 ] This hydrogelcoated mesh effi ciently removed water from water-oil mixtures and did not become fouled with oil.…”
Section: Doi: 101002/admi201500650mentioning
confidence: 99%
See 2 more Smart Citations
“…Following this strategy, many mesh and porous materials that are underwater superoleophobic have been fabricated, and these materials have been successfully applied in oil-water separation. [18][19][20][21][22][23][24][25] For example, Jiang and co-workers coated microscale porous stainless steel mesh with a nanostructured hydrogel to give a novel underwater superoleophobic rough mesh. [ 18 ] This hydrogelcoated mesh effi ciently removed water from water-oil mixtures and did not become fouled with oil.…”
Section: Doi: 101002/admi201500650mentioning
confidence: 99%
“…Problems that have not been adequately addressed are the cost of the materials, the equipment required, and the preparation processes required -all of which prevent large-scale applications. Another issue is that the most widely used materials are metal meshes and porous polymers that have rough microscale-nanoscale hierarchical structures, which are generally formed using chemical corrosion or other chemical methods, [20][21][22][23][24][25] meaning that solving one environmental problem (oil pollution) could cause another (disposing of the waste produced to create the superoleophobic material). It is therefore very important that we develop or fi nd stable materials that are underwater superoleophobic and can be used to simply, cheaply, and effi ciently separate large amounts of oil-water mixtures.…”
Section: Doi: 101002/admi201500650mentioning
confidence: 99%
See 1 more Smart Citation
“…The smart surfaces are typically being responsive toward the change of certain environmental cues such as temperature [1,16,17], light illumination [18,19], pH [2,[20][21][22], chemical compositions [23][24][25][26], solvents [27,28], and applied bias voltage [29][30][31]. However, the surfaces with reversible wettability controlled by some of the previously used approaches require a long time conversion, even several weeks [32], which limits their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic channels and oilwater separation are a few examples [1], [2]. Kobayashi et al have shown that the combination of hydrophilic-hydrophobic surfaces can lead to surface wettability differences and liquid manipulation.…”
Section: Introductionmentioning
confidence: 99%